Telling the Story of Rally Driver Michele Mouton’s Career in the Form of a Comic Media - Paquito, Kenneth; Septian Rachman, Vicky (International Journal of Art, Design, and Metaverse, 2024)
Although Rallying is one of the most recognizable motorsport in the world, its popularity has been in a decline since 1997, including Indonesia. Citizens nowadays pay more attention to sports that are advertised more in entertainment media. The lack of attention and awareness towards the challenges and excitement of rallying makes it a niche motorsport. To expand the market for rallying media, a rallying-themed comic that tells the story of Michèle Mouton, Group B racer, will be made. The book explores Michèle’s career in rallying, as well as the excitement and issues she faced. The book will help readers understand factors that relates to things Michèle had faced, based on a storyline that is easy to digest, fun to read and educative. It is hoped that a rallying-themed comic book can introduce readers to the motorsport and help understand rally racers’ skills and challenges in championships they participate in.